2013
DOI: 10.1097/prs.0b013e318287a072
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Use and Impact on Plastic Surgery Practice

Abstract: This study depicts current patterns of social media use by plastic surgeons, including motivations driving its implementation and impressions on its impact. Many feel that social media are an effective marketing tool that generates increased exposure and referrals. A small number of surgeons have experienced negative repercussions from social media involvement. Our study reveals the presence of a void. There is a definite interest among those surveyed in developing best practice standards and oversight to ensu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
100
3
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 155 publications
(115 citation statements)
references
References 6 publications
3
100
3
4
Order By: Relevance
“…This response rate is comparable to that of recent plastic surgery surveys regarding social media. [6][7][8] Of these 123 surveys, group 1 (Facebook users) completed 56 and group 2 (Facebook nonusers) completed 67, resulting in response rates of 11.2 percent and 13.4 percent, respectively (p > 0.05). Survey completion was defined as answering the mandatory questions (demographics, Facebook impact) at a minimum.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…This response rate is comparable to that of recent plastic surgery surveys regarding social media. [6][7][8] Of these 123 surveys, group 1 (Facebook users) completed 56 and group 2 (Facebook nonusers) completed 67, resulting in response rates of 11.2 percent and 13.4 percent, respectively (p > 0.05). Survey completion was defined as answering the mandatory questions (demographics, Facebook impact) at a minimum.…”
Section: Resultsmentioning
confidence: 97%
“…[9][10][11][12] However, few studies have elucidated the impact of social media on the individual practitioner. 6,7 In 2011, Wheeler et al found that 28 percent of board-certified plastic surgeons used social media for their practice. 6 More recently, Vardanian et al demonstrated that Facebook is the leading online networking platform used by plastic surgeons.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations